UE side Application Layer metrics For QoE-based Network Management. - Tarrías Muñoz, Antonio; Moreno Sancho, Alejandro Antonio; Baena-Martínez, Eduardo; Barco-Moreno, Raquel; Fortes-Rodríguez, Sergio; Pareja Peña, Francisco Javier (My University, 2023)
Cellular networks are being improved by the automation of management tasks in order to optimize the performance while improving the efficiency. This is based on the vast amount of data which is available from the network side. Nonetheless, the network side perspective is limited and the focus is being redirected to the user side. Here, Drive Tests are in charge of collecting useful information, but at high costs. Thus, the present work presents a key source of information regarding network management: user side application layer metrics. In this regard, this work exploits this user side data by using different techniques to estimate the users’ quality of experience with the aim of network management.
Keywords: Sistemas de comunicaciones móviles; Telecomunicaciones; Application layer; UE side; QoE; ML